Perbedaan Pola Pikir Orang Indonesia dan Orang Prancis melalui Karya Terjemahan - Sajarwa Sajarwa (Deskripsi Bahasa, 2018)
Transfer of message in the translation process is always characterized by the difference of culture in the source language and the target language. Language, as a part of culture, affects the speaker mind including translator. Text of French literature (as source text, ST) and text of Indonesian literature (as target text, TT) could be an example of difference in mindset of French people as writer of French literature and Indonesian people as translator. The study results showed the differences in the mindset throught analyzes of (i) Active-Passive Construction of French pronoun on and passive di-, (ii) dominantly pronoun as means of topics continuity in French and repetition in Indonesian, and (iii) the difference ofinformational arrangement looked in impersonal construction of French with pattern of IL+IB and IB+IL in Indonesian.